SISTEM KONTROL PERANGKAT LISTRIK HEMAT ENERGI PADA BANGUNAN BERBASIS BERBASIS INTERNET OF THINGS (IoT) - Yunus Tjandi; Zulhajji (SEMINAR NASIONAL DIES NATALIS 62, 2023)
Accidents caused by improper use of electricity have been widely aired on TV media and On Line media. To prevent this, it is hoped that people who install electrical installations must be certified and are expected to know about how IoT-based energy-efficient control devices work. This research aims to: 1) To create an Energy-Saving Electrical Device Control System Software in IoT-Based Buildings that functions to control the use of electrical energy in a building with the help of a Smartphone, 2) produce an Energy-Saving Control System Device using the software that has been created, 3) To create an Interface and Application of the Internet Of Things (IoT) Based Energy Saving Control System device with the help of a Smartphone that functions to control electrical devices in buildings, both from a short distance, and remotely. Data collection in this study uses interview techniques with control experts, literature techniques, and direct measurement techniques of the control devices used. The data analysis method used in this research is the logical method, based on the Internet of Things (IoT) based control system. The results showed that: 1) The Internet Of Things (IoT)-based Energy Saving Control System Software created has functioned properly, this is evidenced by the functioning of all control systems, both in the safety system (MCB), as well as for various controlled loads, 2). The Internet Of Things-based Energy Saving Control System device made, has functioned properly, this is evidenced in the research trial using a Smartphone, 3). Interface and Control System Applications based on the Internet of Things have functioned properly, because they have been able to control electrical equipment devices contained in a building according to design.